Developing an automated cash flow statement application - Chia, Sheng Chi (2008)
The problem of this study was to identify, elicit and consolidate criteria/opinions useful in the development of an Automated Cash Flow Statement (CFS) Application. As proof-of-concept, a prototype was developed using MS Access.